2004
DOI: 10.1677/joe.0.1800055
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-beta is the predominant estrogen receptor subtype in human oral epithelium and salivary glands

Abstract: Many studies have shown that the oral mucosa and salivary glands are sensitive to estrogen action. However, the expression of estrogen receptors (ERs) within these tissues is an area of controversy. ERs exist as two subtypes (ER and ER ), and we hypothesized that the incongruity between ER expression and estrogen sensitivity may result from differential expression of ER subtypes in oral tissues. To test this hypothesis, we analyzed oral mucosal and salivary gland samples for ER and ER protein expression by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
155
2
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(174 citation statements)
references
References 40 publications
(53 reference statements)
8
155
2
9
Order By: Relevance
“…In addition, MMP-26 can cleave ER-b in vitro and plays an important antitumorigenic role in hormoneregulated malignancies by regulating the amount of ER-b and thus regulating the oestrogen signalling pathway (Savinov et al, 2006). In this study we found, for the first time, that although ER-b, but not ER-a, are expressed in normal oral mucosa (Välimaa et al, 2004) they were both faintly produced in the tongue SCC islands. ER-b is expressed by lymphocytes (Törnwall et al, 1999;Ulziibat et al, 2006), and interestingly we found a weak correlation for the expression of ER-b in inflammatory cells with prolonged survival.…”
Section: Discussionmentioning
confidence: 51%
“…In addition, MMP-26 can cleave ER-b in vitro and plays an important antitumorigenic role in hormoneregulated malignancies by regulating the amount of ER-b and thus regulating the oestrogen signalling pathway (Savinov et al, 2006). In this study we found, for the first time, that although ER-b, but not ER-a, are expressed in normal oral mucosa (Välimaa et al, 2004) they were both faintly produced in the tongue SCC islands. ER-b is expressed by lymphocytes (Törnwall et al, 1999;Ulziibat et al, 2006), and interestingly we found a weak correlation for the expression of ER-b in inflammatory cells with prolonged survival.…”
Section: Discussionmentioning
confidence: 51%
“…Some organs (lung, bladder, intestines) and glands (prostate, pituitary) differ in their expression, with ERβ being greater than ERα [60,[64][65][66]. Notably, within tissues, the distribution of ERα and ERβ can also vary.…”
Section: Erβ-mediated Actions In the Hippocampus For E 2 'S Functionamentioning
confidence: 99%
“…Hypoestrogenic and hyperglycaemic effects cause the loss of the balance in the body's defence system that induces oxidative stress. In addition, oestrogen supports salivary gland cell maturation and has activating effects on secretion [3]. Diabetes can cause dehydration and inadequate blood glucose control, resulting in the hypofunction of the salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogen receptors are found in the cells of many tissues belonging to the reproductive system organs, brain, kidney, heart, bone, and salivary glands [1][2][3]. These receptors serve as transcription sites for the hormones that function in the area of DNA binding sites.…”
Section: Introductionmentioning
confidence: 99%